Reduction of proton acceleration in high-intensity laser interaction with solid two-layer targets - Wei, MS; Davies, JR; Clark, E; Beg, F; Gopal, A; Tatarakis, M; Willingale, L; Nilson, P; Dangor, A; Norreys, P; Zepf, M; Krushelnick, K (2006)
Reduction of proton acceleration in the interaction of a high-intensity, piosecond laser with a 50-μm aluminum target was observed when 0.1-6 μm of plastic was deposited on the back surface (opposite side of the laser). The maximum energy and number of energetic protons observed at the back of the target were greatly reduced in comparison to pure aluminum and plastic targets of the same thickness. This is attributed to the effect of the interface between the layers. Modeling of the electron propagation in the targets using a hybrid code showed strong magnetic-field generation at the interface and rapid surface heating of the aluminum layer, which may account for the results. © 2006 American Institute of Physics.